The Mediating Role of Opportunity of Participation Impact in Determining Training Effectiveness among Potential Entrepreneurs in Business Organisations - Adamu, Muhammad (American Finance & Banking Review, 2017)
The main objective of this study is to evaluate the training effectiveness on potential entrepreneurs through opportunity of participation given on a task in an organisation. The methodology used in this study is a survey research design through a quantitative approach. Questionnaires are used in collecting data in a cross-sectional survey. The data was analysed using the special package for social sciences (SPPS). Pearson’s correlation co-efficient and regression analysis were conducted. Sobel test was also conducted to confirm the mediating effect of opportunity of participation. The findings revealed that there is a positive relationship between training effectiveness (Kirkpatrick Four Levels) and potential entrepreneur’s performance. The regression analysis indicates opportunity of participation has been a dominant factor in the relationship between training effectiveness and potential entrepreneur’s performance. The integration of a mediator in the frame contributes to Kirkpatrick model in the extant training and development as well as entrepreneurship literature. Furthermore, policy makers and HR departments of business organizations will have more appreciation of how training can be appropriately evaluated more particularly, the on-the-job training for an improved performance.